2016
DOI: 10.9734/jaeri/2016/24602
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Nine Medicinal Plants against Aspergillus species from Cocoa Beans (Theobroma cacao)

Abstract: Aims:The study was to screen the activities of nine medicinal plants against Aspergillus species isolated from stored cocoa bean seeds collected in Akure, Owo, Ondo, Ile-Oluji, Ikpenmen, and Oba-Akoko, all in Ondo State, Nigeria with a view to getting a potent, cheap antifungal plant that is easily available and capable of halting fungal infestation and subsequent mycotoxin production. Place and Duration:The study was carried out in Adekunle Ajasin University, Akungba-Akoko between July, 2014 to November, 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The results of this study are in line with the results of a study by [21] suggesting that ginger extract was able to inhibit the growth of Aspergillus foetidus, Aspergillus versicolor, Aspergillus carbonarius, and Aspergillus nidulan at 31, 59, 64, and 73 % when compared to controls. Ginger extract with a concentration of 15 % can inhibit the growth of mycelia Alternaria mold by 57 % when compared to controls [22].…”
Section: Extract Concentration Colony Diameter (Mm) Percentage Of Inh...supporting
confidence: 91%
“…The results of this study are in line with the results of a study by [21] suggesting that ginger extract was able to inhibit the growth of Aspergillus foetidus, Aspergillus versicolor, Aspergillus carbonarius, and Aspergillus nidulan at 31, 59, 64, and 73 % when compared to controls. Ginger extract with a concentration of 15 % can inhibit the growth of mycelia Alternaria mold by 57 % when compared to controls [22].…”
Section: Extract Concentration Colony Diameter (Mm) Percentage Of Inh...supporting
confidence: 91%
“…Barra-Bucarei et al [35] suggested that the action of B. bassiana as an endophyte increases the plant's ability to resist the attack of pathogens such as B. cinerea and Fusarium ssp [36]. In tomatoes, chili peppers and maize plants, B. bassiana acts as an opportunistic parasite on various phytopathogens, as it has pathogenic and saprophytic habits.…”
Section: Discussionmentioning
confidence: 99%
“…Radial growth of pathogenic fungi in the presence or absence of the endophyte was measured after 7 days, and antagonistic percentage (A) was calculated using the following formula: A (%) = CDC-CDT / CDCx100, where CDC represents the colony diameter growth (mm) of the control plate and CDT represents the colony growth diameter of pathogen on the test plate (Abdennabi et al, 2017). According to Nuangmek et al (2008) and Orole and Adejumo (2009), if the antagonistic percentage is: a) less than 30%, the antifungal activity of the endophytes is low; b) between 30 and 50%, the antifungal activity is moderate; c) between 50 and 70%, the activity is high and d) above 70%, the activity is very high.…”
Section: Antagonistic Activity Of Endophytesmentioning
confidence: 99%
“…Endophytes modulate the plant's immune system and increase the production of secondary metabolites by its host plant (Khare et al, 2018). Some of the endophytes like Trichoderma koningii and Alternaria alternata from maize roots have antagonistic effects on Fusarium pathogen (Orole and Adejumo, 2009). Banana endophytes inhibited the growth of Fusarium oxysporum f. sp cubense and Colletotrichum guaranicola (Souza et al, 2013).…”
Section: Introductionmentioning
confidence: 99%